Efektivitas Ekstrak Edamame (Glycine Max L. Merril) terhadap Streptococus Mutans pada Kawat Orthodontik Berbahan Nikel Titanium - Padelia Padelia; Purwanto Purwanto; Leliana Sandra Deviade Putri (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Tooth movement in Orthodontic is brought about orthodontic archwire, which generate the biomechanical forces, transmit these forces via brackets to bring about tooth movement. Niti wire are the most commonly used in orthodontic treatment. These devices have characteristics that can lead to plaque accumulation. This study aims to assess the effectiveness of edamame extract (Glycine max L. Merril) Against Streptococcus Mutans (S. mutans) on orthodontic Nickel Titanium (NiTi). This study was an in vitro laboratory experimental study with a posttest only control group design. Edamame were extracted using the maceration method using 70% ethanol. NiTi immersed in artificial saliva in order to form pellicles for bacterial adhesion. NiTi that has been formed pellicles are then contaminated with S. mutans bacterial suspension, then cleaning is done by immersing in distilled water and edamame extract (Glycine Max L. Merril) with a concentration of 50, 75 and 100mg/ ml then observation is carried out by counting the number of colonies. with the Total Plate Count (TPC) method. The results showed that the smallest average number of S. mutans colonies was found in the edamame extract concentration of 75 and 100mg/ml. The statistical results showed that there was a significant difference between the 75 mg / ml edamame extract group and the negative control. Edamame extract with concentration of 50 mg/ml is an effective concentration in inhibiting the growth of S.Mutans bacteria.